Effect of time in function on the predictability of short dental implants (≤6 mm): A meta‐analysis. (6th January 2020) - Vazouras, Konstantinos; de Souza, Andre Barbisan; Gholami, Hadi; Papaspyridakos, Panos; Pagni, Sarah; Weber, Hans‐Peter
Abstract: Purpose: To analyse randomised controlled clinical trials (RCTs) and prospective cohort studies reporting on the survival and failure rates of functionally loaded short implants (SI) based on the actual length of time in function. Materials and methods: This meta‐analysis was conducted according to PRISMA guidelines for systematic reviews. Electronic and manual searches were conducted to identify RCTs and prospective cohort studies reporting survival and complication rates of short dental implants (≤6 mm) based on the time in function. Secondary outcomes included the location (maxilla or mandible), type of restoration (single crown [SC] versus fixed dental prosthesis [FDP]) and marginal bone loss (MBL). Results: A total of 20 studies (11 RCTs and 9 prospective) fulfilled the inclusion criteria and featured a total of 1238 SI placed in 747 patients. The overall (early and late) mean percentage of short implant failure was 4%. SI with up to 1‐year follow‐up presented failure rate of 2%, while SI followed up for >3 years showed a failure rate of 10%. SI restored with SC presented a late failure rate of 4% while SI restored with FPD 2%. The late failure rate did not differ in terms of location (maxilla or mandible) both with 3%. Conclusion: Short implants in function for more than 3 years presented higher failure rates compared to SI in function for <3 years. Splinting crowns supported by SIs in the posterior area should be considered. However, SI is a valid option for selected cases given their relatively high long‐term survival rates.